Factors predicting self-reported medication low adherence in a large sample of adults in the US general population: a cross-sectional study. Issue 6 (23rd June 2017) - Feehan, Michael; Morrison, Margaux A; Tak, Casey; Morisky, Donald E; DeAngelis, Margaret M; Munger, Mark A
Abstract : Objectives: The study objective was to determine the level and correlates of self-reported medication low adherence in the US general population. Setting: A 30 min cross-sectional online survey was conducted with a national sample of adults. Participants: 9202 adults (aged 18+) who had filled at least three or more prescriptions at a community pharmacy in the past 12 months. Primary and secondary outcome measures: Self-reported medication adherence was measured with the 8-item Morisky Medication Adherence Scale. Results: Low adherence was reported by 42.0%, 29.4% had medium adherence and 28.6% had high adherence. Low adherence was significantly associated with: lower age, being of Hispanic origin or African-American, having difficulty with healthcare, medication or transportation costs, needing the support of others to access primary care, health limiting activity, using multiple providers, infrequent visits to primary care providers and visiting an emergency department >3 times in last 12 months. Conclusions: A very high level of low medication adherence is seen in the general population, particularly for ethnic minorities, those who use multiple healthcare providers and those who experience barriers to access for regular primary care. As clinical, patient education and counselling, and healthcare policy initiatives are directed to tracking the problem of low medication adherence, these should be priority populations for research and interventions.